12(x-3)=6(2x+2)-48

Simple and best practice solution for 12(x-3)=6(2x+2)-48 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12(x-3)=6(2x+2)-48 equation:


Simplifying
12(x + -3) = 6(2x + 2) + -48

Reorder the terms:
12(-3 + x) = 6(2x + 2) + -48
(-3 * 12 + x * 12) = 6(2x + 2) + -48
(-36 + 12x) = 6(2x + 2) + -48

Reorder the terms:
-36 + 12x = 6(2 + 2x) + -48
-36 + 12x = (2 * 6 + 2x * 6) + -48
-36 + 12x = (12 + 12x) + -48

Reorder the terms:
-36 + 12x = 12 + -48 + 12x

Combine like terms: 12 + -48 = -36
-36 + 12x = -36 + 12x

Add '36' to each side of the equation.
-36 + 36 + 12x = -36 + 36 + 12x

Combine like terms: -36 + 36 = 0
0 + 12x = -36 + 36 + 12x
12x = -36 + 36 + 12x

Combine like terms: -36 + 36 = 0
12x = 0 + 12x
12x = 12x

Add '-12x' to each side of the equation.
12x + -12x = 12x + -12x

Combine like terms: 12x + -12x = 0
0 = 12x + -12x

Combine like terms: 12x + -12x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| y=2x+30 | | 7+6(3n+7)=85 | | T=10/(2/7) | | 5m^2-70m+225=0 | | -7+y=-19 | | 9=n+9/3 | | -1+8(1+7x)=-273 | | 2y^2+x-32y+133=0 | | 12c-625=35 | | x^2+3x+12=-4x | | (6x+17)=143 | | 6(3+2b)+7b=151 | | 3x+6x+9x=9 | | x+72=65 | | (x-4)+(3x+1)-x=180 | | 6+5(-7n-8)=176 | | X^2+6x+9+y^2-12y+36=4 | | 3m/4+2/3=m/2+7/8 | | 4p-2=-5p+5 | | x^2-22x=9 | | 2s-1/4=1u1/3 | | 5(5+3m)=115 | | 17.2*x^2+1.58x-.2025=0 | | 8x+16=-48 | | 2x^2-1=5 | | 3/4-(2/3*1/3+1/9)+4/9 | | 5y+5x=10graph | | p-4=19+p | | N/7+11/14=17/14 | | 6-6(1+5x)=90 | | 9x^2+18x+9=25 | | 2x+4-3=6 |

Equations solver categories